Transpopliteal Balloon-Assisted Excimer–Laser Atherectomy for the Treatment of Chronic Femoropopliteal Occlusions: Feasibility and Initial Results. Issue 8 (January 2014) - Lüdtke, Christopher W.; Scheer, Fabian; Kamusella, Peter; Wissgott, Christian; Andresen, Reimer
Purpose: Recanalization of chronic total occlusions (CTOs) of the femoropopliteal arteries depends on a successful lesion crossing with the guide wire. The aim of this retrospective study was to evaluate the safety, feasibility, and the primary results of retrograde recanalization of CTOs with balloon-assisted excimer–laser atherectomy (ELA) via a transpopliteal approach after failed antegrade attempts. Methods: A total number of 15 patients (10 male, 5 female) with a mean age of 68.5 years (range: 43-91 years) treated with retrograde transpopliteal ELA in the years 2009-2012 were included retrospectively. After unsuccessful antegrade recanalization attempts with conventional guide wires and catheters, patients were treated with a retrograde recanalization attempt via a transpopliteal access using an excimer laser, followed by pressure-only balloon angioplasty (POBA). The mean length of the CTOs in the femoropopliteal arteries was 17.8 ± 5.4 cm (range: 9-29 cm). Results: Technically successful recanalization was achieved in 14 of 15 patients. Provisional stenting was done in two cases. There were no major adverse events regarding the laser atherectomy or popliteal access site. One acute reocclusion was observed in the first 48 hours after intervention. The ankle-brachial Index increased from preinterventional 0.45 ± 0.07 to 0.77 ± 0.29 ( P < 0.05) in the follow-up period (1.5 months), resulting in a primary patency of 80%. Conclusion: The retrograde ELA for recanalization of chronic femoropopliteal occlusions via a popliteal access turned out to be a safe and effective procedure with promising primary results. Thus it may be an endovascular treatment option for long chronic occlusions after failed antegrade recanalization or in patients who are not suitable for surgery.